Efecto de la inclusión de diferentes niveles de maralfalfa (pennisetum spp.) como fuente de fibra, sobre la calidad de la canal en cuyes - Criollo Rios, Fernanda del Cisne (2023)
Guinea pig breeding is one of the main activities in the Andean countries, so obtaining a quality product is crucial for producers, for this reason the present research evaluated the effect of the inclusion of different levels of Maralfalfa (Pennisetum spp.) as a source of fiber, on the quality of the carcass in guinea pigs. A total of 120 weaned guinea pigs, 60 males and 60 females, type A1, were distributed in eight experimental groups of 15 animals each, according to a 4x2 factorial arrangement (diets x sex); for a period of 60 days, they were fed diets containing 0, 2, 16 and 31% of Maralfalfa. Data were recorded for live weight, carcass weight, carcass yield, muscle pH and meat color at 24 hours after slaughter; the data were processed and subjected to analysis of variance and protected t-test. The statistical analysis did not determine interaction between the factors under study; therefore, the results are presented separately for each sex. The carcass yield, males showed higher results with (72%) in the diet with 2% inclusion of maralfalfa; while in females no statistical difference was detected with a mean of (67.4%); The pH in muscle was taken from the biceps femoris, which showed no difference between diets with a mean in males of 5.94 and in females of 5.93; likewise, the color of the meat showed no variation due to the effect of the diets, with values of L=53.89; a*=5.59; b*=-6.02 in males and L=52.34; a*=6.42; b*=-5.42 in females. It is concluded that the inclusion of 2% of maralfalfa has a positive influence on carcass yield; however, the different levels of maralfalfa in the diet do not influence muscle pH and meat color. Keywords: maralfalfa, guinea pigs, carcass, pH, color.